2015
DOI: 10.1080/10408398.2013.834874
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Lactic Acid Bacteria and Skin Health

Abstract: Human skin is the first defense barrier against the external environment, especially microbial pathogens and physical stimulation. Many studies on skin health with Lactic acid bacteria (LAB) have been published for many years, including prevention of skin disease and improvement of skin conditions. LAB, a major group of gram-positive bacteria, are known to be beneficial to human health by acting as probiotics. Recent studies have shown that LAB and their extracts have beneficial effects on maintenance and impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 66 publications
0
39
0
2
Order By: Relevance
“…Some studies [82,147] have found that postoperative consumption of probiotics (mainly L. plantarum 299) per os improves immune response, reduces the number of postoperative infections, and reduces hospitalization time and the amount of prescribed antibiotics. All of these studies conclude that postoperative endpoints should continue to be thoroughly investigated, and two studies went on to highlight the great potential of topical use of probiotics to protect the wound [15,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies [82,147] have found that postoperative consumption of probiotics (mainly L. plantarum 299) per os improves immune response, reduces the number of postoperative infections, and reduces hospitalization time and the amount of prescribed antibiotics. All of these studies conclude that postoperative endpoints should continue to be thoroughly investigated, and two studies went on to highlight the great potential of topical use of probiotics to protect the wound [15,17].…”
Section: Discussionmentioning
confidence: 99%
“…Using various state-of-the-art molecular and genetic-based methods, it was found that the skin microbiota is dominated by bacteria from the phyla Actinobacteria, Firmicutes, Proteobacteria, and Bacteroidetes; resident genera mainly include Propionibacterium spp., Staphylococcus spp., Micrococcus spp., Corynebacterium spp., and Acinetobacter spp. and the main representatives of the fungi being species of the genus Malassezia [15][16][17][18]. e diversity of skin microbiota among individuals depends on age, diet, gender, and environmental and geographical factors.…”
Section: Skin Microbiotamentioning
confidence: 99%
“…Plant stanols and sterols, which lower serum concentrations of cholesterol, have been incorporated into foods, but they are expensive (Law, 2000). Over the years, the probiotic activity of lactic acid bacteria (LAB) has been studied (Collins, 2014), and LAB have been associated with improved lactose intolerance, increased natural resistance to infectious disease in the gastrointestinal tract, the suppression of cancer, and better digestion and skin health (Lye et al, 2010;Clarke et al, 2012;Kanmani et al, 2013;Zhong et al, 2014;Jeong et al, 2016). Moreover, Mann and Spoerry (1974) and Shaper et al (1963) evidenced the hypocholesterolemic effects of a diet containing LAB strains, and it has been proven that some LAB can lower total cholesterol and low-density lipoprotein cholesterol levels (Zeng et al, 2010;Ishimwe et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the health-promoting activities of lactic acid bacteria are species- and strain-specific [10]. Thus, use of a variety of lactic acid bacteria as a dietary supplement has been investigated extensively [11], and interest in the use of lactic acid bacteria for improvement of skin conditions has been growing [12]. Some reports show beneficial effects on atopic dermatitis or allergic rhinitis [13, 14], skin aging [15], and acne [16].…”
Section: Introductionmentioning
confidence: 99%